Benefits of adding a physician-staffed ambulance to bystander-witnessed out-of-hospital cardiac arrest: a community-based, observational study in Niigata, Japan - Tasuku Matsuyama; Nobuhiro Sato; Kohei Akazawa; Kyoko Nakazawa; Yasuo Hirose (BMJ Open)
Objective This study aimed to assess the benefits of adding a physician-staffed ambulance to bystander-witnessed out-of-hospital cardiac arrest using a community-based registry.Design Population-based, retrospective cohort study.Setting An urban city with approximately 800 000 residents.Participants Patients aged ≥18 years with bystander-witnessed out-of-hospital cardiac arrests of medical aetiology in Niigata City, Japan, between January 2012 and December 2016, according to the Utstein style.Primary and secondary outcome measures The primary outcome was 1-month survival with a favourable neurological outcome, defined as a cerebral performance category score of 1 or 2. We used logistic regression analysis to assess the association between favourable neurological outcome and prehospital physician involvement.Results During the study period, a total of 4172 cardiac arrests were registered; of these, 892 patients with out-of-hospital cardiac arrest were eligible for this analysis, among whom 135 (15.1%) had prehospital physician involvement and 757 (84.9%) did not have prehospital physician involvement. The percentage of favourable neurological outcomes was 20.7% (28 of 135) in those with physician involvement and 10.4% (79 of 757) in those without physician involvement (p=0.001). Using multivariable logistic regression, prehospital physician involvement had an OR for a favourable neurological outcome of 3.44 (95% CI 1.64 to 7.23).Conclusions Among adults with out-of-hospital cardiac arrest, adding a physician-staffed ambulance was associated with significantly greater favourable neurological outcomes than standard emergency medical services.